N′-[(E)-2-Hydroxy-3,5-diiodobenzylidene]cyclohexane-1-carbohydrazide - Thirugnanasundar, A. (International Union of Crystallography, 2011)
In the title compound, C(14)H(10)I(2)N(2)O(2), the two aromatic rings are inclined at a dihedral angle of 16.72 (33)°. The molecular structure is stabilized by an intramolecular O—H⋯N hydrogen bond. In the crystal, intermolecular N—H⋯O interactions link the molecules into chains running along the c axis. C—H⋯O interactions also occur. The crystal used for the structure determination was a non-merohedral twin with a domain ratio of 0.972 (2):0.028 (2).